Ṣadaqa and ‘Spirituality Gene’ Expression: The Qurʾan and Advances in Epigenetics - Edi Basuki; Naqiyah Naqiyah (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
Charity  (ṣadaqa) is commonly given for religious reasons: Muslims donate voluntarily to earn Allah’s pleasure and receive His blessings. However, there have been changes in the way Muslims perceive charity and what significance it has in their life. Many studies have addressed this issue but failed to explore the connection between ṣadaqaand mental state. This paper was aimed to complement the existing studies by analyzing the process of the shifting interpretation of charity and its positive effects on the donors. This study used qualitative analysis of primary and secondary data. The data was processed through descriptive methods and content analysis. In particular, it focused on analyzing the religious background of the donors, including the biological processes underlying their tendency to give generously. The study concluded that the practice of giving ṣadaqa increases social, emotional, and spiritual wellbeing, depending on the level of spirituality of the donors and their intention.